(untitled) (Revista de Ciências Agroveterinárias, 2006)
A survey of management of medicinal plants by rubber-tappers at Extractive Reserve Chico Mendes, State of Acre, was carried out. Researchs like this are rare in Acre, particularly in Extractive Reserves, which are territories set asid e since 1987 by Federal Government for sustainable use and conservation of renewable natural resources by communities with primarily extractive economies. The research was intended to rescue and to systematically record the local informations about different management techniques on medicinal plants, in different environments, anthropic or natural, resulting in informations to futher projects of economical exploration, with ecological and technological adequation, with data to further research projects and public health and to help to maintain and and h ighlight the value of popular knowledge about medicinal plants and to contribute to their conservation. The field work was done between November/1991 to November/1997, in 18 seringais of Extractive Reserve Chico Mendes, at municipalities of Brasiléia and Xapuri, Acre, with 53 interviews. The research contributed to high the comprehension of the local health situation, cultural identity, importance of forest and medicinal plants and so, it is hoped this work will help the rubber-tappers to maintain these Reserves and their people.